(3VhA GdeHGQcs ((3CMeO aVd Gddg GdCefGci s)
(3ChdgG (B:s
(3CeGHYO MeO Gddg Pi GdEfYGe , CeG cdeI ajgG eYfi GdTQW adPdc cGfJ GdaGA dGReI dgG , bGd SjHhjg bhdge CeG RjO aefWdb eYfGg eYgeG jcf ef TF aRjO efWdb s
(3BNQgG (B:s
(3hgPG HGH ddEWfGH ajg eLGd dcfg jaVi Edi GdedGd aGbJUQJ Ydi gPG GdbOQ hGddg CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdfMhs